KONTRIBUSI SYEKH AHMAD MUTAMAKKIN DALAM PROSES ISLAMISASI DI JAWA - Manggara Bagus Satriya Wijaya (Jantra., 2017)
Using hermeneutical approach, this qualitative research looks at the values embedded in the exemplary characters of Sheik Akhmad Mutamakkin. The data were drawn from the Kajen text. The result shows that Sheikh Akhmad Mutamakkin has applied eclectic and conformative methods of Sufism. He has blended Islamic tradition and local tradition (Java). Therefore, he cannot be categorized as misguided ulama so that there is no need to revise any writings about him. The conclusion of this study can also be used as a negation that Sheikh Akhmad Mutamakkin is not a heretic. The reason why he is said as heretical in Serat Cebolek is caused by political factors and ideological conflict between puritan Islam and eclectic Islam that accomodates Javanese traditions.